Circular Polarization in Nature: Factual, Theoretical and Experimental Summary - Berthier, Serge; Thomé, Magali; Simonis, Priscilla (Materials today : proceedings, 2014)
Circular polarization of light created by living organisms has recently been the subject of renewed interest. At the origin is the discovery, in a marine arthropod, of a visual device sensitive to this state and able to distinguish the left circular polarization from the right one. Numerous other organisms that produce circularly polarized light by reflection, mainly beetles of the Scarabaeidae family, have also been identified and biologists now want to test their sensitivity to this polarization state. Along with this, the experimental techniques used to characterize the polarization states of light, as well as the structures that generate them, have significantly evolved. We present here the different sources of circular polarization found in nature, animal origin or not, as well as the theoretical bases for their study. Different experimental techniques are then quickly presented.